A model for incorporating suitable methods of usability evaluation into agile software development - Fouad Abdulameer Salman; Aziz Deraman (Bulletin of Electrical Engineering and Informatics, 2022)
The challenge to incorporate usability evaluation values and practices into agile development process is not only persisting but also systemic. Notable contributions of researchers have attempted to isolate and close the gaps between both fields, with the aim of developing usable software. Due to the current absence of a reference model that specifies where and how usability activities need to be considered in the agile development process. This paper proposes a model for identifying appropriate usability evaluation methods alongside the agile development process. By using this model, the development team can apply usability evaluations at the right time at the right place to get the necessary feedback from the end-user. Verification of the proposed model was conducted using the focus group method by experts from industry domain.